TANTANGAN PESANTREN SALAF DI ERA MODERN - Wahyu Iryana (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2015)
Abstract: One of the distinctive teaching of science in schools is the transformation of the yellow book that discusses the science instrument. In the broader science of translation tools include traditional Arabic grammar, such as nahwu (sintakstis), sharf (inflection), balaghah (rhetoric), in addition there is also a mantiq science (logic) and tajwid (science to read the Koran well and right). However, over the age of the modern world today through a lot of big changes, especially information and communication technology developments. Seeing the rapid development of the world is for many people has led to mixed response. No exception for Muslims and no exception boarding school in it. Changes that continue to appear lately in it touches almost all aspects of human life, economic aspects to the aspect of moral values. Simply put, this global era can be illustrated by the fierce competition in the field of science and politics, the progress of science and technology, the rapid flow of information, and high social change. The research results can be 3 things that could strengthen the pesantren First, tamaddun of promoting boarding. Secondly, Tsaqafah, namely how to give enlightenment to the Muslims so that creative-productive in religious life, by not forgetting the originality of Islam. Third, hadara, namely establishing a culture. In this case, how our culture can be characterized by the spirit and traditions of Islam.